Multiple signatures of criticality explored on V1 neuronal activity - SILVA, Thaís Feliciano (2023)
The hypothesis that the brain self-organizes around a critical point has been under in- vestigation for nearly three decades. This notion posits that extensive neuronal populations can be effectively examined as many-body systems, characterized by principles from statistical physics. According to this analogy, a system near this critical point exhibits certain func- tional advantages, and the brain already exhibits these characteristics, providing support for the concept of brain criticality. In other contexts, critical point analysis typically explores the transitions between various phases or states of a system, yet the application of this analysis to the dynamics of the brain has remained relatively underexplored. In this study, we propose the evaluation of three distinct signatures of criticality for different cortical states. We define different cortical states based on the level of variability in neuronal population activity, which is closely associated with the degree of synchrony among neurons. The criticality indicators demonstrate greater significance during moments characterized by intermediate levels of syn- chronization among the neuronal population, as recorded using silicon probes in the visual cortex of anesthetized rats. These findings reinforce investigations into fundamental questions such as the self-organization of brain dynamics around a critical point between assumed brain states and also into the use of synchrony levels in neuronal population activity as an order parameter for a transition associated with the critical point.